Management of educational resources development in improving the quality of education in elementary school - Jhon Hendri; Edi Harapan; Dessy Wardiah (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aims to identify and describe the management of educational resource development in improving the quality of education at the 14 Air Kumbang State Elementary School. With a qualitative descriptive research method, the use of qualitative descriptive research design in this study is intended to describe and analyze the management of educational resource development in improving the quality of education at 14 Air Kumbang State Elementary Schools. The technique of collecting data in this research is through interviews, observation, documentation and triangulation. The results showed that the steps for implementing human resource development management were planning, organizing, actuating, and controlling. The obstacles faced in the implementation of human resource development in improving the quality of education at the Air Kumbang 14 Public Elementary School are: lack of teacher consistency (in absenteeism, seriousness in training). The effect of these constraints in the implementation of training is that the results obtained are not optimal, the results are not in accordance with what is expected and can reduce the RABM and in training are also limited by funds